Improvement of the workplace environmental physical factors values monitoring by determining the optimal interval for their control - Kruzhilko, O. Ye.; Polukarov, O. I.; Kalinchyk, V. P.; Tkalych, I. M.; Кружилко, О. Є.; Ткалич, І. М. (Association for Computational Materials Science and Surface Engineering, 2019)
Determination of such an interval of workplace environmental physical factors control, which would ensure high monitoring reliability and the minimum data collection and processing duration (or cost).
Keywords: Safety and health management; Workplace environmental physical factors; Algorithmization